Changes in the histological structure of tissues and organs of pikeperch (Sander lucioperca Linnaeus, 1758) and perch (Perca fluviatilis Linnaeus, 1758) from the Zaporizhzhia Reservoir under the influence of human impact - P. Korzhenevska; T. Sharamok; A. Doroshenko (Ribogospodarsʹka Nauka Ukraïni)
Purpose. The aim of the study was to investigate morphological and histological features of the gills, liver and blood of percids – pikeperch (Sander lucioperca Linnaeus, 1758) and perch (Perca fluviatilis Linnaeus, 1758) from different areas of the Zaporizhzhia Reservoir.